Is Fear of Missing Out Related to Neuroticism? A Meta-Analysis Study: Apakah Fear of Missing Out Benar Terkait dengan Neurotisisme? Sebuah Studi Metaanalisis - Rahardjo, Wahyu; Mardianti (Universitas Islam Indonesia, 2023)
The observation of the progress made in studying “fear of missing out” is interesting, specifically with a focus on analyzing the possible existence of a strong correlation between the concept and the antecedents widely involved in most of these studies such as neuroticism. This meta-analysis was conducted to measure the correlation between neuroticism and fear of missing out by considering the size of the effect. The process involved using 13,685 participants from 23 eligible studies as samples. The results showed that neuroticism was positively correlated to fear of missing out at a moderate strength as indicated by r = .369 and 95% CI (.29, .44). Similar results were also found for adolescents and emerging adulthood groups (95% CI [.272, .460]) as well as the common group and workers (95% CI [.249, .488]). Moreover, the heterogeneity test showed good significance, the distribution of scores was considered symmetrical except in adolescents and emerging adulthood, and no publication bias was detected. The moderate level of correlation reported showed the possibility of involving neuroticism as an antecedent of fear of missing out. However, the effect could become stronger when it was involved with other external antecedents.